Detection of Some Virulence Factors in Candida albicans Obtained From Different Clinical Specimens of Iraqi Patients - Rasheed Majeed AL-Rubaie, Sukayna; Ahmed Al-Qaysi, Safaa Al-Deen (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The Candida albicans is a diploid polymorphic yeast that is found as part of the normal microbial flora in most healthy humans. It’s usually a harmless colonizer of mucosal surfaces; it can, however, cause disease in the case where the host suffers from a weakened immune system or is immunocompromised. The present investigation was carried out to detect and investigate the prevalence of some virulence factors, which include coagulase production, biofilm formation, and phospholipase distribution among Candida albicans isolated from different clinical samples, including oral cavity and respiratory tract, which were collected from May to August 2022 and numbered 280 of different ages and genders of Iraqi patients suspected of respiratory diseases and candidiasis. After detection, among the 102 positive samples, results showed that 58 (56.86%) were from the oral cavity and 44 (43.14%) were from the respiratory tract. Candida albicans was the most prevalent species among the six types collected of Candida species, while Candida glabrata was the least prevalent. All of the yeast was identified using several conventional methods, such as chlamydospore generation and germ tube production, and grown on HiCrome Candida medium, which was confirmed using the VITEK-2 system. Biofilm activity was strong in 34 (48.57%) of Candida albicans isolates, while 45 (64.29%) strong isolates produced phospholipase and 59 (84.29%) isolates had the ability to produce coagulase.